Redescription and relationships of Pseudothilmanus Pic (Coleoptera: Rhagophthalmidae)—a long-term neglected glow-worm beetle genus from the Himalayas - Kundrata, Robin; Bocak, Ladislav (Zootaxa, 2011)
Pseudothilmanus Pic, 1918 is redescribed and two species, P. alatus Pic, 1918 and P. marginatus Pic, 1918, are placed in the genus. The subgenus Drilothilmanus Pic, 1918 is synonymized with the nominotypical genus on the basis of low morphological divergence and redundancy in classification. Pseudothilmanus is newly classified in the family Rhagophthalmidae, in contrast to the original placement in Drilidae. Diagnostic characters for Pseudothilmanus and both species placed within the genus are illustrated.